Making Cards - Watt, Fiona; Illustrated By Non Figg, Antonia Miller (Usborne, 2006)
This text features cards for birthdays, Christmas, Easter and Valentine's Day, along with techniques and methods for creating artistic effects on the cards themselves. Every card in this title is illustrated in a colourful style, with step-by-step instructions.
Include Illusrtation And Index
Keywords: Cards Making